Remote sensing archaeology knowledge transfer: Examples from the ATHENA twinning project - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Nisantzi, Argyro; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Mamouri, Rodanthi-Elisavet; Mettas, Christodoulos; Evagorou, Evagoras G.; Themistocleous, Kyriacos; Papgeorgiou, Nicoletta; et al. (My University, 2018)
ATHENA is an on-going Horizon 2020 Twinning project aiming to promote remote sensing technologies for cultural heritage (CH) applications in Cyprus. ATHENA project brings together the Eratosthenes Research Center (ERC) of the Cyprus University of Technology (CUT) with two internationally leading institutions of Europe, namely the National Research Council of Italy (CNR) and the German Aerospace Centre (DLR). The project's scope is to position the ERC regionally and stimulate future cooperation through placements at partner institutions and enhance the research and academic profile of all participants. The scientific strengthening and networking achieved through the ATHENA project could be of great benefit not only for Cyprus but for the entire Eastern Mediterranean, bearing a plethora of archaeological sites and monuments urgently calling for monitoring and safeguarding. The preservation of CH and landscape comprises a strategic priority not only to guarantee cultural treasures and evidence of the human past to future generations, but also to exploit them as a strategic and valuable economic asset. The objective of this paper is to present knowledge transfer examples achieved from the ATHENA project through intense training activities. These activities were also designed to enhance the scientific profile of the research staff and to accelerate the development of research capabilities of the ERC. At the same time the results from the training activities were also exploited to promote earth observation knowledge and best practices intended for CH. The activities included active and passive remote sensing data used for archaeological applications, Synthetic Aperture Radar (SAR) image analysis for change and deformation detection, monitoring of risk factors related to cultural heritage sites including archaeological looting etc.
Keywords: Archaeology; ATHENA; Space technologies; Training activities; Twinning project